1983
DOI: 10.4141/cjps83-087
|View full text |Cite
|
Sign up to set email alerts
|

THE BIOLOGY OF CANADIAN WEEDS.: 58. Galinsoga parviflora and G. quadriradiata (= G. ciliata).

Abstract: A summary of biological information is provided on two species of Galinsoga — G. parviflora (small-flowered galinsoga) and G. quadriradiata (hairy galinsoga). Originating in Central America, both species are weeds of disturbed habitats and agricultural areas, occurring in most of the temperate and subtropical regions of the world. In recent years the galinsogas have become troublesome weeds of low-growing vegetable crops in northeastern North America. The two species serve as alternate hosts for many insects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
3

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 2 publications
6
35
0
3
Order By: Relevance
“…Hairy galinsoga, the species named as most problematic and most risky by New England vegetable farmers, lacks dormancy in the soil 45 . Incorporate the cost of time and labor and crop quality along with reduced yield to better represent economic impact of weed management strategy for farmers .…”
Section: Farmer Beliefs Communication/research Recommendationsmentioning
confidence: 99%
“…Hairy galinsoga, the species named as most problematic and most risky by New England vegetable farmers, lacks dormancy in the soil 45 . Incorporate the cost of time and labor and crop quality along with reduced yield to better represent economic impact of weed management strategy for farmers .…”
Section: Farmer Beliefs Communication/research Recommendationsmentioning
confidence: 99%
“…In later years, flushes occurred after cultivations, especially in April, but there was also sporadic emergence at other times and the seeds were relatively persistent. Warwick & Sweet (1983) concluded that since there is little or no dormancy, infestations can often be eliminated in 3-4 years. Some seeds of Galinsoga parviflora sown in August gave rise to seedlings in September and October and more began to appear in March.…”
Section: Emergence Mainly In Autumn: Seeds Persistentmentioning
confidence: 99%
“…Galinsoga species occupy fields, gardens, railways and ruderal sites and may also invade seminatural habitats such as forest paths, clearings and margins in woodlands (Tokarska-Guzik, 2003Chmura, 2004;Kabuce and Priede, 2010a;Trzcińska-Tacik et al, 2010). Galinsoga species pose a threat to crop production by competing with cultivated plants and also by acting as alternate hosts for many insects, viruses and nematodes that affect crop species (Warwick and Sweet, 1983). Because it is an aggressive weed, Galinsoga has attracted the interest of several researchers, including embryologists.…”
Section: Galinsoga Quadriradiatamentioning
confidence: 99%